Identification of Flavonoids and Phenolic Compound in Aloe Vera gel by HPLC - Ilham Nazhan Numan (Tikrit Journal of Pure Science, 2023)
Flavonoids and Phenolic Compounds are  important Components For Aloe Vera gel .The HPCL analysis proved that Aloe Vera gel contains many types of phenolic compounds (188.79 mg/ml cinnamic acid ,876.44 mg aloin, 555.01 Aloe emodin, 235.096 Aloeecticacid, 252.52 Anthranol, 549.98 Simapic acid) at Retention Times (1.777, 3. 448, 5.273, 6.192, 7.378, 8.765) min and Area (54348, 231817, 188319, 71949, 88097, 153061) and many types of flavonoids (227.48 Quercetin, 236.23 Kaempherol, 247.65 Rutin)at Retention Times (1.89,3.15,7.493,8.413) and Area (75828,66531,88538,125858